Implementasi E-Kinerja terhadap Penilaian Kinerja PNS di Kabupaten Banyuwangi - Rania, Gita (Penerbit Goodwood, 2024)
Purpose: This study aimed to evaluate how the electronic performance appraisal system (e-kinerja) is implemented for civil servants in the Banyuwangi Regency. It specifically focuses on assessing its effectiveness and enhancing accountability in performance evaluation. Methodology: This research was conducted in the Banyuwangi Regency using a qualitative approach. It involved in-depth interviews with civil servants and literature review to gather information on the implementation of the e-kinerja system. The tools used included interview guides to collect data from the participants and relevant documents to support the analysis. Results: The findings indicate that the e-Kinerja system significantly improves transparency and accountability in performance assessments, achieving a user adoption rate of 95%. However, many civil servants initially struggled with the new technology, which limited their ability to effectively use the system. This emphasizes the need for ongoing training and support in digital skills to help all users fully utilize the features of the system. Overall, this research provides valuable insights into the implementation of e-government initiatives, especially in enhancing performance evaluations in the public sector. Limitations: This study was limited to a single regency, which may affect the generalizability of the findings to other regions. Additionally, reliance on qualitative data may introduce a subjective bias. Contributions: This study offers valuable insights into e-government initiatives for enhancing performance evaluations in the public sector, emphasizing the importance of training and support in technology adoption.